Effect of drying methods on yield, physicochemical properties, and total polyphenol content of chamomile extract powder - Lee, Sin Yee; Ferdinand, Vincent; Siow, Lee Fong (Frontiers in Pharmacology, 2022)
The aim of this study was to determine the effect of drying methods (convection oven-drying, freeze-drying, and spray drying) on powder yield, physicochemical properties (moisture content, water activity, and color attributes), and total polyphenol content of chamomile extract powder. Our findings showed that spray-drying conducted at 140°C, 12 mL/min resulted in the lowest yield of powder (16.67 %) compared to convection oven-drying (90.17 %), and freeze-drying (83.24 %). Decreasing the feed flow rate to 10.5 mL/min during spraying caused an increase in powder yield to 26.99 %. The moisture content of spray-dried chamomile extract powder obtained at 140°C, 10.5 mL/min was higher (11.00 %) compared to that of convection oven-dried (8.50 %) and freeze-dried (7.50 %). Both convection oven-dried and freeze-dried chamomile extract powder displayed no significant difference (p > 0.05) in moisture content. The higher feed flow rate (12 mL/min) in spray-drying also led to an increase in moisture content of chamomile extract powder to 12.00 %. The higher residual moisture found in the spray-dried samples had resulted in partial agglomeration of particles. In terms of water activity, freeze-dried chamomile extract powder was found to have the highest water activity (0.63) compared to that of convection oven-dried (0.52), spray-dried at 140°C, 10.5 mL/min (0.57), and spray-dried at 140°C, 12 mL/min (0.58). Spray-dried and freeze-dried chamomile extract powder with high moisture content and water activity could be highly susceptible to microbial growth. In terms of color attributes, higher drying temperature in spray-drying led to darker, redder, and more yellowish chamomile extract powder that could be caused by heat-induced Maillard reaction and caramelization. Since lower drying temperature was used in both convection oven-drying and freeze-drying, both convection oven-dried (56.94 mg GAE/g powder) and freeze-dried chamomile extract powder (55.98 mg GAE/g powder) were found to have higher total polyphenol content compared to those of spray-dried (42.79 to 46.79 mg GAE/g powder). Due to a high powder yield with ideal powder properties such as low moisture content and water activity, desirable color, and high total polyphenol content obtained from convection oven-drying, convection oven-drying was preferred over freeze-drying and spray-drying for drying chamomile extract.